2014
DOI: 10.1007/s00187-014-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between CEO work, management accounting information, and financial performance: evidence from Finnish top managers

Abstract: The objective of this study is to analyze the association between CEO work, importance of management accounting information (MAI), and financial performance of the firm. The research model is based on nine hypotheses on the association of CEO work with traditional dimensions of managerial tasks (time span, process stage, and functional area), importance of MAI, and financial performance. We assume that CEO work is directly associated with the importance of MAI, but also indirectly mediated by traditional task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Another approach given to investigations of behavioral characteristics is the role of what organizations expect from managers (the management style put on work functionsinterpersonal, informational, and decisional). Such information can help associating certain types of management with the use of MCS (Laitinen, 2014).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach given to investigations of behavioral characteristics is the role of what organizations expect from managers (the management style put on work functionsinterpersonal, informational, and decisional). Such information can help associating certain types of management with the use of MCS (Laitinen, 2014).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The characteristics of the managerial role played specifically by the CEO is also one of the factors associated with the use of MCS because information is a key element of a manager's work, consuming more than half of their daily activities on average. The complexities of the management role affect how managers choose, project, and use information (Laitinen, 2014). can see the use of managerial controls in a diagnostic and interactive way (Laitinen, 2014).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAI provides the information to an organization's various departments, spanning from decision-making to organizational learning. MAI is the basic source of information for an organization's planning, decision-making, and monitoring (Ahmad, 2012;Laitinen, 2014). Bakar (2018) and Hui and Yusof (2010) reported that it is helpful and vital to managers in assisting their decision-making, performance appraisal, and communication with their colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…MAI provides information for various purposes spanning from decision-making to as a means of organisational learning. MAI is the basic source of information for an organization's planning, decision-making and monitoring (Ahmad, 2012;Laitinen, 2014). Abu Bakar (2001), and Hui and Yusof (2010) reported that it is helpful and vital to managers in assisting their decision-making, performance appraisal and communication.…”
Section: Introductionmentioning
confidence: 99%